Variability in the carbon isotope composition of individual amino acids in plant proteins from different sources: 1 Leaves. (May 2016) - Lynch, Anthony H.; Kruger, Nicholas J.; Hedges, Robert E.M.; McCullagh, James S.O.
Graphical abstract: Radar plot shows normalised natural-abundance 13 C isotope values of individual amino acids from plant leaf proteins vary consistently between plant groups, but are little influenced by season, environment or species. Values that are significantly greater in either forbs or grasses are indicated in red and blue, respectively. Highlights: δ 13 C values of amino acids in plant leaf proteins vary with plant functional group. Seasonal and environmental fluctuations do not affect amino acid δ 13 C variation in leaf protein. Variation between amino acid δ 13 C values can be correlated with plant functional group. Variation in the pattern of amino acid δ 13 C can be useful in palaeodiet and ecosystem studies. Abstract: The natural carbon isotope composition of individual amino acids from plant leaf proteins has been measured to establish potential sources of variability. The plant leaves studied, taken from a range of plant groups (forbs, trees, grasses, and freshwater aquatic plants), showed no significant influence of either season or environment (water and light availability) on their Δδ 13 C values. Plant groups did, however, differ in carbon isotope composition, although no consistent differences were identified at the species level. A discriminant analysis model was constructed which allowed leaves from (1) nettles, (2) Pooideae, (3) other Poales, (4) trees and (5) freshwater higher plants to be distinguished from each other on the basis of their natural abundance 13 C/ 12 C ratios of individual amino acids. Differences in carbon isotope composition are known to be retained, to some extent, in the tissues of their consumers, and hence an understanding of compound-specific variation in 13 C/ 12 C fractional abundance in plants has the potential to provide dietary insights of value in archaeological and ecological studies.